Floristic diversity and dominance patterns of Sal (Shorea robusta Gaertn. f.) forests in North Western Himalayas: implications for conservation and sustainable management - Aditi Sharma; D. R. Bhardwaj; C. L. Thakur; Naveen Katoch; J. P. Sharma (Frontiers in Forests and Global Change, 2025)
The floristic composition of Sal forests is paramount for biodiversity and environmental resilience. Monitoring species diversity contributes to conservation and sustainable management. Considering this, the present study was undertaken to assess the floristic composition and diversity of Shorea robusta-dominated stands in the Paonta Forest Range of Himachal Pradesh. Sample plots of 0.1 ha were laid out (systematic random sampling) in seven compartments, recording 33 genera with 34 species belonging to 26 families. The results revealed that the flora of compartments catalogued with Lai C28 had the maximum (9) tree species, Kukron C15 and Rajban C10 had the maximum shrub species, and Rajban C6 and Rajban C7 had maximum herb species among all the compartments. S. robusta was the dominant species, with IVI varying between 126.72 and 156.59 in the compartments. The similarity index of trees in compartments ranged from 0.67 to 1.00. Rajban C6 and Rajban C7 had the maximum similarity index. This research focused on documenting the diversity of plants within the Sal Forest of Himachal Pradesh, India, and produced valuable scientific data and a fundamental understanding for the conservation of biodiversity and sustainable management.